Star wars: the high republic adventures phase ii (2022), volume 2 ebook - Older, Daniel José (Star Wars: The High Republic Phase II (2022), 2023)
The Battle of Jedha, the biggest event in the High Republic cross-platform initiative, reaches its climax in this stunning conclusion to Star Wars: The High Republic Adventures, Phase II! As the Jedi Order desperately tries to end the conflict that rages through the streets of the Holy City, Padawan Sav Malagan struggles to maintain her secret identity as she tries to free captain Maz Kanata from the clutches of the Dank Graks. As Arkik Von's dark plan plays out, Sav will have to make the most difficult decision of her young life: duty to the Force, or loyalty to her friends? The clash between the Light and the Dark side threatens to consume the galaxy in Star Wars: High Republic Adventures Volume 2, collecting issues 5-8, written by New York Times bestselling author Daniel José Older with artists Harvey Tolibao and Toni Bruno! Great for readers of ALL AGES!